Rancang Bangun Virtual Try-On Baju Adat Pernikahan Kabupaten Padang Pariaman - Amelia Luthfiah Hanum; Sheanny Ocmi Sakti (Lembaga Yasin AlSys, 2026)
Although the digitalization of cultural heritage opens new opportunities for introducing traditional clothing, the use of virtual try-on to represent traditional wedding attire of Padang Pariaman Regency remains limited. This study aimed to design and develop a markerless augmented reality-based Virtual Try-On application displaying the attire of Anak Daro, Marapulai, Bundo Kanduang, Niniak Mamak, and Pasumandan. The study employed a research and development approach using the Multimedia Development Life Cycle model, which includes the concept, design, material collecting, assembly, testing, and distribution stages. This study did not involve participants as the main unit of analysis because it focused on product development. Data were collected through observation, documentation, literature review, and functional testing. Three-dimensional clothing models were created using Blender and integrated into Unity 2022.3.0f1, while MediaPipe Pose Landmarker was used to detect 33 body points through a webcam and control the position, scale, orientation, and movement of the models in real time. The results showed that all main functions of the application could be executed in accordance with the designed workflow. This study produced a cultural visualization medium that can be utilized in exhibitions and educational activities. Thus, this study contributes to the development of interactive technology-based media for introducing traditional clothing, while further testing needs to involve more diverse users and develop Face Mesh, depth estimation, and cloth simulation features.